Pengembangan Modul Berbasis SETS (Science, Environment, Technology, and Society) Berbantuan Quick Response Code (QR-Code) pada Materi Hidrokarbon Kelas XI SMA/MA - Rumaysa, Najma Andzar; Dalimunthe, Makharany (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
The research on the development of SETS (Science, Environment, Technology, and Society)-based modules assisted by QR-Code (Quick Response Code) on hydrocarbon material aims to: 1) determine the feasibility of the developed module in accordance with BSNP standards; 2) determine the response of students to the module; and 3) determine the effectiveness of the developed module on student learning outcomes on hydrocarbon material. The research method used is Research & Development (R&D) with the 4D model (Define, Design, Develop, and Disseminate). The final product is a printed module that is tested for module feasibility by material experts and media experts, as well as response tests and effectiveness tests by 29 students of class XI IPA 1 SMA Cerdas Murni. The results of the percentage of module feasibility in the overall study were 88.81% in the feasible category, in content feasibility 88.06%, presentation feasibility 89%, language feasibility 89.5%, and graphic feasibility 88.67%. The results of the percentage of overall student responses were obtained at 88.09% in the very high category, and in the interest aspect 86.36%, the material aspect 89.16%, and the language aspect 88.74%. The effectiveness of the module on student learning outcomes with the N-Gain test obtained an average of 0.78 in the high category, and the module was effective in improving learning outcomes. It can be concluded that the SETS (Science, Environment, Technology, and Society)-based module assisted by QR-Code on hydrocarbon material is feasible to use and gets a positive response in its use, and is effective in improving student learning outcomes.